Influence of the content and particle size of rice husk ash on the water susceptibility of asphalt mixtures (SCIÉNDO INGENIUM, 2025)
This study investigates how rice husk ash (RHA) content and particle size influence the water susceptibility of asphalt mixes. A two-factor experiment was conducted, varying RHA proportions (2.5%, 5.0%, and 7.5%) and particle sizes (149, 74, and 53 µm). The RHA, sourced from agro-industrial wastes in Trujillo, Peru, was previously analyzed by, scanning electron microscopy (SEM) showed irregular, porous, and angular particles, typical of ashes produced at moderate temperatures, which enhance binder interaction and internal friction. The ash analysis also identified crystalline phases like cristobalite and quartz, suggesting chemical reactivity. Coarse and fine aggregates met Peruvian standards for durability and wear resistance. The optimal asphalt cement content was 4.39%, balancing cohesion, stability, and air voids. The experimental results indicate that adding 5.0% RHA, especially with particle sizes smaller than 53 µm, significantly improves the mixture's resistance to moisture damage. This not only enhances the longevity of pavements but also promotes sustainability by incorporating waste materials into road construction. The incorporation of RHA not only improves the technical performance of asphalt mixtures, but also represents an environmentally beneficial strategy by reusing an abundant agricultural waste, reducing the environmental impact and promoting a circular economy.
Keywords: asphalt mixtures; water susceptibility; rice husk ash; stability; TSR Test